Pengaruh gaya kepemimpinan kepala madrasah dan budaya kerja terhadap disiplin kerja guru - Wilda, Abraham; Ahyani, Nur; Rahman, Andi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
Leadership is a way of doing something to achieve certain goals, as well as the leadership of the principal which is carried out in order to achieve educational goals. In line with leadership that shapes work culture, ultimately leadership and work culture are believed to be able to shape the characteristics of optimal work discipline. The study was conducted to determine the effect of the madrasa principal's leadership style and work culture on teacher’s work discipline. The method used in this research is descriptive quantitative, with data obtained through questionnaires and documentation. Data analysis was performed through simple and multiple linear regression. The results obtained from this study stated that 1) there was a significant influence of the madrasa principal's leadership style on the work discipline of MTs teachers in Pangkalan Lampam District; 2) there is a significant influence of work culture on the work discipline of MTs teachers in Pangkalan Lampam District; 3) there is a significant influence on the leadership style of the madrasa principal and work culture together on the work discipline of MTs teachers in Pangkalan Lampam District.